Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1177/0265407597142001
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy and Connectedness as Dimensions of Relationship Styles in Men and Women

Abstract: This study identified a trichotomy of styles that characterize adults' relationships with partners: self-focused autonomy, other-focused connection, and mutuality. Each style was defined by several dimensions; dominance-submission, whose needs are met, sensitivity to the partner's feelings, clarity of feelings, separateness vs intimacy, and concern with the relationship. Participants were adults, aged 18-70 years, who responded to a newspaper survey in which they identified their own style of relationship and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 11 publications
1
31
0
1
Order By: Relevance
“…Adopting the perspective that orientations towards autonomy and connectedness are too sharply dichotomized, Harter et al (1997) conducted a study that examined three distinct relationship styles within spousal or partner relationships: self-focused autonomy (an overemphasis on autonomy at the expense of connection), other-focused connection (an overemphasis on connection at the expense of autonomy), and mutuality (a balanced integration of concerns with autonomy and connection). Individuals with a self-focused autonomous style in relationships tend to emphasize the self's needs and feelings and have a strong sense of separateness from their partner.…”
mentioning
confidence: 99%
“…Adopting the perspective that orientations towards autonomy and connectedness are too sharply dichotomized, Harter et al (1997) conducted a study that examined three distinct relationship styles within spousal or partner relationships: self-focused autonomy (an overemphasis on autonomy at the expense of connection), other-focused connection (an overemphasis on connection at the expense of autonomy), and mutuality (a balanced integration of concerns with autonomy and connection). Individuals with a self-focused autonomous style in relationships tend to emphasize the self's needs and feelings and have a strong sense of separateness from their partner.…”
mentioning
confidence: 99%
“…NOTE 1. Although the three relationship styles may seem similar to Hazan and Shaver's (1987) adult attachment styles, Harter et al (1997) found that the two measures were not significantly associated, demonstrating that the two typologies concern different relational constructs.…”
Section: Discussionmentioning
confidence: 76%
“…Although the exact cause for these cultural differences is unclear, they certainly highlight the circumstance that the internal feelings of individuals often oppose prevailing cultural norms (Turiel, 2002). Finally in the present study, we examined the link between the three relationship styles and psychological well-being to determine whether mutuality would be associated with the best outcomes for Mexican Americans as previous researchers have found with European Americans (Harter et al, 1997;Neff & Harter, 2002. The present results indicated that the mutuality style led to significantly better outcomes for both ethnic groups in relationship satisfaction, perceived validation, voice, self-worth, and depressed affect than did the SFA and OFC styles (which did not differ significantly from each other).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations